ARF-derived peptide sensitizes ovarian cancer cells to Cisplatin - Zhou, Jinhua; Wang, Yunfei; Qian, Yun; Wang, Xinran; Liu, Ting; Di, Wen (Translational Cancer Research, 2018)
Background: Forkhead box M1 (FOXM1) is over-expressed in multiple cancers, and its over-expression induces chemoresistance and contributes to unfavorable prognosis in patients with ovarian cancer. P19ARF is a tumor suppressor that contains a motif, which suppresses the transcriptional activity of FOXM1. In this study we investigated the potential role of alternative reading frame (ARF)-derived peptide as a cisplatin sensitizer for ovarian cancer. Methods: FOXM1 expression in ovarian cancer tissues were analyzed using the online databases Oncomine and protein atlas. The association between FOXM1 expression and cisplatin response was analyzed and plotted in a panel of ovarian cancer cell lines. The expression of FOXM1 downstream target genes were accessed in SKOV3 cells treated with ARF peptide using quantitative polymerase chain reaction (QPCR) and western blot. Clonogenicity and apoptosis in SKOV3 cells treated with ARF peptide in the presence or absence of cisplatin was used to evaluate the effect of ARF peptides. In addition, tumor size in nude mice bearing SKOV3 xenografts were measured in the presence or absence of wild-type or mutant ARF peptide and with or without cisplatin. Results: FOXM1 was over-expressed in ovarian cancer tissues and cell lines. FOXM1 expression was associated with cisplatin response in the ovarian cancer cell lines. ARF peptide decreased both mRNA and protein expression of FOXM1 downstream target genes, polo-like kinase 1 (PLK1) and exonuclease 1 (EXO1). In vitro, SKOV3 cells pretreated with ARF peptide showed increased apoptotic cells, decreased clonogenicity, and increased cleavage of caspase-3 in response to cisplatin treatment. In vivo, combination of wild-type ARF peptide and cisplatin had increased inhibition of tumor growth compared to mutant peptide. Conclusions: FOXM1 expression levels are associated with cisplatin response. Treatment with ARF peptide enhanced cisplatin sensitivity in ovarian cancer cells. These results suggest a new therapeutic strategy to overcome chemoresistance in FOXM1 overexpressing ovarian cancers.